Understanding online revisions in L2 writing: A computer keystroke-log perspective. (November 2018) - Xu, Cuiqin
Abstract: Revising, as a fundamental component process of written text production, has drawn extensive research attention in second language (L2) writing. While most studies examined revisions through sociolinguistic categories to understand how revisions cognitively load on L2 writers, further studies need to quantify the cognitive deployment of attentional resources during revising. Using Inputlog6.0, this study investigated the online revisions of 57 Chinese EFL writers at the more- and less-skilled writing levels. Online revisions were first divided into immediate, distant and end revisions according to their temporospatial locations, and then examined in terms of frequency, scope, duration, distance and in relation to the final text quality. Data analysis revealed that less-skilled L2 writers revised more frequently but on smaller scopes in immediate and distant revisions, while more-skilled L2 writers revised more frequently and on larger scopes in end revisions. The text quality correlated negatively with the frequencies of immediate and distant revisions, yet positively with the scopes of all three types of online revisions and with all four dimensions of end revisions. These findings suggest that, while writing is a recursive process when different component processes interact, L2 writers benefit from a focused production process scaffolded by in-depth and extensive revising processes.